Depression in non-alcoholic fatty liver disease is associated with an increased risk of complications and mortality - Ng, Cheng Han; Xiao, Jieling; Chew, Nicholas W. S.; Chin, Yip Han; Chan, Kai En; Quek, Jingxuan; Lim, Wen Hui; Tan, Darren Jun Hao; Loke, Ryan Wai Keong; Tan, Caitlyn; Tang, Ansel Shao Pin; Goh, Xin Lei; et al. (Frontiers in Medicine, 2022)
Background & Aims The global prevalence of non-alcoholic fatty liver disease (NAFLD) is expected to rise continuously. Furthermore, emerging evidence has also shown the potential for concomitant depression in NAFLD. This study aims to examine the prevalence, risk factors and adverse events of depression in NAFLD and evaluate whether treated depression can reverse the increased risks of adverse outcomes. Methods This study analyses the 2000-2018 cycles of NHANES that examined liver steatosis with fatty liver index. The relationship between NAFLD and depression was assessed with a generalized linear mix model and a sensitivity analysis was conducted in the no depression, treated depression and untreated depression groups. Survival analysis was conducted with cox regression and fine grey sub-distribution model. Results 21,414 patients were included and 6,726 were diagnosed with NAFLD. The risk of depression in NAFLD was 12% higher compared to non-NAFLD individuals (RR:1.12, CI:1.00-1.26, p=0.04). NAFLD individuals with depression were more likely to be older, females, Hispanics or Caucasians, diabetic and higher BMI. Individuals with depression have high risk for cardiovascular diseases (CVD) (RR:1.40, CI:1.25-1.58, p<0.01), stroke (RR:1.71, CI:1.27-2.23, p<0.01), all-cause mortality (HR:1.50, CI:1.25-1.81, p<0.01) and cancer-related mortality (SHR:1.43, CI:1.14-1.80, p=0.002) compared to NAFLD individuals without depression. The risk of CVD, stroke, all-cause mortality and cancer-related mortality in NAFLD individuals with treated depression and depression with untreated treatment was higher compared to individuals without depression. Conclusion This study shows that concomitant depression in NAFLD patients can increase the risk of adverse outcomes. Early screening of depression in high-risk individuals should be encouraged to improve the well-being of NAFLD patients.